2005
DOI: 10.1088/0954-3899/31/10/060
|View full text |Cite
|
Sign up to set email alerts
|

Yrast structures in the light Pt isotopes169–173Pt

Abstract: The exploitation of the recoil-decay tagging (RDT) technique has reinvigorated experimental investigations of the shape coexistence phenomenon in heavy neutron-deficient nuclei. In a recent experiment using the JUROGAM and GREAT spectrometers in conjunction with the RITU gas-filled separator, excited states have been investigated in the light platinum isotopes. In addition to extending the yrast sequences in 170Pt and 172Pt, the first observation of excited states in the odd-N isotopes, 169Pt and 173Pt, is rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
(13 reference statements)
1
4
0
Order By: Relevance
“…m D 0), which is consistent with RDSD observations at larger sample sizes approaching the scale of a radar volume (e.g. Joss and Gori 1978) and assigning N 0 D 8000 (Marshall and Palmer 1948). For these parameters the coef cients b and k are de ned as follows, where temperature (T / is in Kelvin, and pressure (P / in hPa: a D .T =P / 0:45 C 0:3401;…”
Section: (A) Derivation Of Vertical Air Velocity In Rainsupporting
confidence: 77%
See 1 more Smart Citation
“…m D 0), which is consistent with RDSD observations at larger sample sizes approaching the scale of a radar volume (e.g. Joss and Gori 1978) and assigning N 0 D 8000 (Marshall and Palmer 1948). For these parameters the coef cients b and k are de ned as follows, where temperature (T / is in Kelvin, and pressure (P / in hPa: a D .T =P / 0:45 C 0:3401;…”
Section: (A) Derivation Of Vertical Air Velocity In Rainsupporting
confidence: 77%
“…Waldvogel (1974) examined the minute-to-minute variation of raindrop size distribution (RDSD, drops >0.3 mm diameter) characteristics derived from disdrometer data in the context of vertically pointing C-band radar. Joss and Gori (1978) showed that the characteristics of the RDSD varied with scale and tended to converge toward an exponential character for longer time periods of several hundred minutes. They hypothesized that precipitation at the scale of a typical scanning radar volume (»1 km 3 / consisted of a mixture of rain rates of different intensities.…”
Section: Structures and Scales Of Precipitation Variat Ionmentioning
confidence: 99%
“…The lowest-lying negative-parity band in 166 Os (band 4) resembles those in nearby nuclei, which have been interpreted previously as structures arising from mixing with low-spin octupole vibrational bands [6,27,46,44]. The low collectivity measured in 166 Os could also allow band 4 to be interpreted in terms of a ν(i 13/2 ⊗ f 7/2 ) multiplet structure.…”
Section: Discussionmentioning
confidence: 54%
“…However, only one transition 17 2 + → 13 2 + was detected experimentally in 169 Pt. [14] Guided by the property of its neighbouring nuclei, we can predict several levels above 17/2…”
mentioning
confidence: 99%
“…On the other hand, yrast band based on the configuration 13/2 + has been established in odd-A 175,173,171 Pt nuclei, [13−15] but experimentally only one transition from 17/2 + to 13/2 + is detected in the extremely neutron deficient nucleus 169 Pt. [14] Besides studying the deformation feature of 177 Pt, we determine the deformation parameters (β, γ) of the odd-A nuclei 175,173,171 Pt by calculating their energy spectra and induce those of 169 Pt by extrapo-lating the trend of the neighbouring nuclei's. In turn, we propose a ground-state band with several low-lying states for 169 Pt in this study.…”
mentioning
confidence: 99%